Home page for accesible maths 6 Chapter 6 contents

Style control - access keys in brackets

Font (2 3) - + Letter spacing (4 5) - + Word spacing (6 7) - + Line spacing (8 9) - +

6.24 Example continued further

Integrating both sides, we obtain

x-1x+1y=dxx+1=log|x+1|+c.\frac{x-1}{x+1}y=\int\frac{dx}{x+1}=\log|x+1|+c.

(Note that the absolute value sign now matters. It is only in the integrating factor that we can ignore it.) Dividing through by x-1x+1\frac{x-1}{x+1}, we obtain the general solution

y=x+1x-1(log|x+1|+c).y={\frac{x+1}{x-1}\left(\log|x+1|+c\right).}

We now want the particular solution satisfying y(0)=1y(0)=1. To obtain this, we evaluate y(0)=1-2(log1+c)=-c2.y(0)={\frac{1}{-2}\left(\log 1+c\right)=-\frac{c}{2}.} Setting this equal to 1, we obtain c=-2c={-2} and therefore the solution is y=x+1x-1(log|x+1|-2).y={\frac{x+1}{x-1}\left(\log|x+1|-2\right).}